Analysis of the scientific works on restructuring of technical base for repair of freight carriages - Bulgakova, J. V. (Science and Transport Progress, 2012)
This article provides an overview of the scientific work to the reformation of the technical basis for repairing the freight carriages during the Soviet period and the need to develop the concept of reforming it in Ukraine.